The composite net-veined diorite intrusives of the Julianehåb district, South Greenland - Windley, B. F. (Meddelelser om Grønland, 1965)
Net-veined diorite intrusive are described from a plutonic environment of Precambrian granites in the Julianehåb district of S. Greenland. They are composite, minor intrusions consisting of a central diorite flanked by margins of aplitic granodiorite and they are characterised by the presence of pillow-shaped diorite blocks form ed by granitic net-veins penetrating from the margins into the central diorite. The net-veins have not chilled the diorite, but along a few there are coarser grained margins in the diorite in which biotite, sphene and orthite have recrystallised. A contraction crack - shear plane theory is proposed to explain the formation of the net-veins. The granite material was introduced along the walls of the bodies from where it penetrated inwards through a network of contraction cracks. It was also introduced through the central parts of bodies along a set of parallel sheet fractures formed by shearing and compression of the diorite. The granitic material was produced by rheomorphism-at-depth from the recently reactivated granites of the Julianehåb district; it followed its basic parent to higher levels, where it penetrated the diorite at least partly by a process of recrystallisation and replacement.